2018
DOI: 10.1093/jbcr/iry043
|View full text |Cite
|
Sign up to set email alerts
|

Development ofPseudomonas aeruginosaBiofilms in Partial-Thickness Burn Wounds Using a Sprague-Dawley Rat Model

Abstract: We used a modified Walker-Mason scald burn rat model to demonstrate that Pseudomonas aeruginosa, a common opportunistic pathogen in the burn ward and notable biofilm former, establishes biofilms within deep partial-thickness burn wounds in rats.Deep partial-thickness burn wounds, ~10% of the TBSA, were created in anesthetized male Sprague-Dawley rats (350-450 g; n = 84). Immediately post-burn, 100 µl of P. aeruginosa in phosphate-buffered saline at 1 × 103, 1 × 104, or 1 × 105 cells/wound was spread over the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
2
28
0
2
Order By: Relevance
“…We recently updated the Walker-Mason rat scald burn model in regards to skin preparation, pain relief, resuscitation regimen, and scald times for both deep partial- and full-thickness burn wound formation 22 . Our previous work showed that, within three days post-burn and surface inoculation with as little as 1 × 10 3 CFU, the opportunistic pathogen P. aeruginosa , when left unimpeded, forms biofilms within deep partial-thickness burn wounds.…”
Section: Introductionmentioning
confidence: 99%
“…We recently updated the Walker-Mason rat scald burn model in regards to skin preparation, pain relief, resuscitation regimen, and scald times for both deep partial- and full-thickness burn wound formation 22 . Our previous work showed that, within three days post-burn and surface inoculation with as little as 1 × 10 3 CFU, the opportunistic pathogen P. aeruginosa , when left unimpeded, forms biofilms within deep partial-thickness burn wounds.…”
Section: Introductionmentioning
confidence: 99%
“…While PNA-FISH staining techniques for tissue have been utilized by many groups in the research field, it is not used extensively in the clinical community. 25,30–32 Limitations to this type of sampling include burn wound integrity, as well as slower turnaround times (about 1–2 days), which are both mitigated by the swab technique. However, if it is possible to collect an intact sample, it may provide further insights into not only the types of pathogens present, but also the depth (ie, tissue penetration) and degree of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo samples were collected from infected burn wounds of male Sprague-Dawley ( n = 3) rats using a previously described model of deep-partial thickness burn infection that was modified to investigate a tri-species infection. 25 In brief, a 10% total body surface area burn (based on Meeh’s formula) 26 was induced on the dorsum of anesthetized rats, followed by immediate surface inoculation of 10 5 CFU/wound of each microorganism ( S. aureus , P. aeruginosa , and C. albicans ; grown to mid-log state) suspended in 1× PBS. On day 3 post-injury, the rats were euthanized and the wound was excised and subjected to biopsy punches, tissue sectioning (histology), and complete swabbing of the entire remaining wound bed as part of sample collection approach.…”
Section: Methodsmentioning
confidence: 99%
“…A DPT or FT scald burn was inflicted on the dorsum of anesthetized rats by methods previously described (Brandenburg et al, 2019b). In brief, the day preceding the burn, male Sprague-Dawley rats weighing 350-450 g were anesthetized with isoflurane (Forane, Baxter Healthcare Corporation, Deerfield, IL, USA) prior to the dorsum being shaved and depilated with Nair (Church & Dwight Co., Inc., Ewing, NJ, USA).…”
Section: Overview Of Scald Burn Modelmentioning
confidence: 99%
“…Following inoculation, wounds were covered with a non-adherent interface dressing, followed by Tegaderm TM Film (3M Health Care, St. Paul, MN). Rats were placed in custom rat jackets (Brandenburg et al, 2019b) to prevent tampering with the wound throughout the study, and monitored over an 11 days period.…”
Section: Overview Of Scald Burn Modelmentioning
confidence: 99%